2012
DOI: 10.1097/cmr.0b013e32835861f6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of delay time between primary melanoma biopsy and sentinel lymph node dissection on sentinel node status, recurrence, and survival

Abstract: For primary melanoma, there is a delay between the initial skin biopsy and sentinel lymph node dissection, which may cause anxiety for the patient. The consequences of this delay on disease progression are unknown. The goal of this study was to determine whether delay time for sentinel node dissection from the initial cutaneous melanoma biopsy affects patient outcomes. A retrospective analysis of 492 patients with melanoma who underwent a sentinel node dissection between 1993 and 1999 was carried out. The endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 18 publications
(16 reference statements)
3
34
1
1
Order By: Relevance
“…To date, only two studies have reported on this topic. Parrett et al found no adverse effects on survival for a time interval of <40 days vs. > 40 days, while Tejera-Vaquerizo et al reported a detrimental effect of a time interval of <40 days at the expense of SN negative patients [11,12]. These contradicting findings are not sufficient to answer the question which effects, if any, time interval may have on survival.…”
Section: Manuscript Text Introductioncontrasting
confidence: 47%
See 1 more Smart Citation
“…To date, only two studies have reported on this topic. Parrett et al found no adverse effects on survival for a time interval of <40 days vs. > 40 days, while Tejera-Vaquerizo et al reported a detrimental effect of a time interval of <40 days at the expense of SN negative patients [11,12]. These contradicting findings are not sufficient to answer the question which effects, if any, time interval may have on survival.…”
Section: Manuscript Text Introductioncontrasting
confidence: 47%
“…SN tumor burden according to the Rotterdam criteria [13,20] is significantly more often high in those patients undergoing SNB after a time interval of 47 days patients from a single institution [12]. With a median time interval of 40 days, no differences in DFS, OS and MSS were found, nor any significant difference in SN positivity rates.…”
Section: Discussionmentioning
confidence: 87%
“…19 Lastly, Parret et al found no difference in OS after analyzing TTI on the basis of groups of patients who waited less than or more than 40 days. 20 …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two studies to date, published by Parrett et al,[3] and at the same time, in this volume, the study of Oude Ophuis et al[16], have studied the impact of the timing of sentinel-node biopsy on survival in melanoma patients. In Parrett’s study, surprisingly, they observed an increased frequency of recurrence and melanoma-specific mortality in patients with a delay time of less than 40 days.…”
Section: Discussionmentioning
confidence: 99%
“…They found no significant differences in survival but the arm of patients treated by immediate lymphadenectomy (n=54) showed a slight tendency to metastasize before with a worse prognosis (n=55). More recently, Parrett et al evaluate the effect of time to sentinel-node biopsy on sentinel-node involvement, recurrence, and mortality, and found no significant differences in survival on comparing a delay time of less than 40 days with one of 40 days or more[3]. They did, however, detect a trend towards higher melanoma-specific mortality in patients who underwent early sentinel-node biopsy (less than 40 days) and attributed this to a higher frequency of ulceration and thicker tumors in this group.…”
Section: Introductionmentioning
confidence: 99%